The Ramos presidency and administration record and legacy, 1992-1998 : President Fidel V. Ramos and his administration - Abueva, Jose Veloso 1928-; Alfiler, Ma. Conception P.; Domingo, Ma. Oliva Z.; Niciolas, Eleanor E. (Second U.P. public lectures on the Philippine presidency and administration, 1998)
Published in 1998 by the University of the Philippines Press, this volume is part of the "Public Administration Record and Legacy Series." It provides a comprehensive, scholarly assessment of the Fidel V. Ramos (FVR) administration, which is widely regarded for its focus on economic liberalization, political stability, and the "Philippines 2000" vision.